Self-management across chronic diseases: Targeting education and support needs. Issue 2 (February 2020) - Bartlett, Susan J.; Lambert, Sylvie D.; McCusker, Jane; Yaffe, Mark; de Raad, Manon; Belzile, Eric; Ciampi, Antonio; Di Carlo, Mario; Lyddiatt, Anne
Highlights: Three types of self-managers were identified. Vulnerable self-managers have the highest task frequency and lowest self-efficacy. The vulnerable group has greater multimorbidity. The vulnerable group differs in preferences for self-management topics. Abstract: Objectives: Among Canadian adults with chronic disease: 1) to identify groups that differ in self-management task frequency and self-efficacy; 2) to compare group characteristics and preferences for self-management support. Methods: Using data from an online survey, cluster analysis was used to identify groups that differed in self-management task frequency and self-efficacy. Multivariable regression was used to explore relationships with patient characteristics and preferences. Results: Cluster analysis (n = 247) revealed three groups: Vulnerable Self-Managers (n = 55), with the highest task frequency and lowest self-efficacy; Confident Self-Managers (n = 73), with the lowest task frequency and highest self-efficacy; and Moderate Needs Self-Managers (n = 119), with intermediate task frequency and self-efficacy. Vulnerable Self-Managers, when compared with the Confident group, were more often: on illness-related employment disability or unemployed; less well educated; diagnosed with emotional problems or hypertension, and had greater multimorbidity. They participated less often in self-management programs, and differed in support preferences. Conclusions: Knowing the characteristics of vulnerable self-managers can help in targeting those in greater need for self-management support that matches their preferences. Practice Implications: Different approaches are needed to support self-management in the vulnerable population.